Institutional Experience with Academic Reform: A Panel Discussion - Evans, John P.; Cartwright, Carol; Alden, Michael; McPhee, Sidney; Anderson, Kevin; Perlman, Harvey (Journal of Intercollegiate Sport, 2012)
This paper consists of the transcripts of a panel discussion focusing on athletic directors’, chancellors’, and presidents’ experiences with academic reform. The panel participants discuss a number of topics, including recent and past academic reform efforts, the process of implementing those initiatives, and the effects of those policies on student athletes and intercollegiate sport.